Development of monopoly media based on QR-Code on the theme of rich my country - Sari, Lusti Indah; Mulyawati, Yuli; Mirawati, Mira (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2023)
This study aims to design and develop QR Code-based monopoly media on the subject matter of my rich country in Class IV SDN Sindang Barang 2 Bogor City. This research method is used to produce several products and to test the effectiveness of these products. The design of this study uses the ADDIE model which consists of the stages of Analysis (Problem Analysis), Design (Product Design), Development (Development), Implementation (Implementation), and Evaluation (Evaluation). This study involved media experts, linguists, and material experts to provide assessments as well as students as media users. The results of this study are that monopoly media based on QR Code has received eligibility validation on the aspect of media suitability based on ISO 9126 quality with a percentage of 83.63%, linguistic aspects by linguists with a percentage of 100%, and material aspects for the sake of material experts with a percentage of 96.36%.. Monopoly learning media based on the QR Code also received a positive response from 33 students with a percentage of 90.8% in the